Sistem Informasi Google Maps Dengan Menggunakan VB.NET - Ricky Ramadhan Harahap; Hidayatullah Hidayatullah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2018)
Google Maps is a web mapping service developed by Google. This service provides satellite imagery, road maps, 3600 panoramas, traffic conditions and route planning for traveling by foot, car, bicycle or public transport. This information system is very helpful in providing information to the community in viewing the area, the address you want to visit and very helpful on the condition that is needed once. The Google MAPS Information System uses the Vb.Net app. Keywords: information system, google map